Prenatal care utilization and infant health in Botswana - David Mmopelwa (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2019)
Despite the freely and publicly provided health care in Botswana, the proportion of low birth weight infants increased from 8% to 13% during 2000-2007 period. The latter rate was among the highest in the WHO African region and upper middle-income countries and may question the effectiveness of care. Using the 2007/08 Botswana Family Health Survey data collected by Statistics Botswana, the paper jointly estimates the adequate prenatal care utilization (input demand) and infant birth weight (outcome) functions through the treatment effect model, which accounts for the binary nature of the endogenous regressor. As birth weight information is not available for all infants, we also estimate a Heckman sample selection model to account for potential bias. Estimating models for rural and urban samples separately, we find that lower levels of mother's education reduces the likelihood to both adequately utilize prenatal care and report infant birth weight. The likelihood for prenatal care utilization increases with the probability of a care facility being sufficiently close and availability of care facilities. Adequate prenatal care utilization is positively associated with birth weight and failing to account for endogeneity reduces its effect. On average, birth weight increases by 0.67, 0.73 and 0.64 kg in full, urban and rural samples respectively.
Keywords: I11; I12; J13; 330; Prenatal care; infant health